Analisis Deskriptif Daya Saing Perguruan Tinggi - Arwildayanto Arwildayanto; Arifin Arifin; Arifin Suking (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2020)
Abstract: The purpose of this study is to describe the competitiveness of the Gorontalo State University colleges in taking policies and strategic steps to improve competitiveness. This research is planned to take place in the next year. For 2020, the method used is a survey to gather information from 174 UNG lecturers about the competitiveness of their place of work, which is taken randomly from 10 existing faculties. From the instrument that was carried out a descriptive descriptive analysis using the Weighted Means Score (WMS) formula, it was found that the competitiveness of UNG was in a fairly good position. This is in line with the ranking carried out by the Ministry of Education and Culture in 2020 UNG is in the order of 86 cluster III. The competitiveness position of UNG provides information on the need for improvement, the hard work of all parties to improve the competitiveness of UNG in accordance with the vision of being superior and competitive. Abstrak: Tujuan penelitian ini mendeskripsikan daya saing perguruan tinggi Universitas Negeri Gorontalo guna mengambil kebijakan dan langkah strategis untuk meningkatkan daya saing ke depannya. Penelitian ini direncanakan berlangsung beberapa tahun ke depan. Untuk tahun 2020 ini metode yang digunakan adalah survey guna menjaring informasi dari 174 orang dosen UNG tentang daya saing tempatnya bekerja yang diambil secara acak dari 10 fakultas yang ada. Dari instrument yang didistribusikan dilakukan analisis deskriptif menggunakan formula Weighted Means Score (WMS), didapatkan data daya saing UNG berada pada posisi cukup baik. Hal ini sejalan dengan pemeringkatan yang dilakukan Kementerian Pendidikan dan Kebudayaan tahun 2020 UNG berada pada urutan 86 klaster III. Posisi daya saing UNG memberikan informasi perlu peningkatan, kerja keras semua pihak untuk menaikan daya saing UNG sesuai dengan visi unggul dan berdaya saing.